Just price in the markets : a history - Geisst, Charles R. (Ascent Audio, 2023)
The question of what constitutes a fair price has been at the center of market interactions since the time of Aristotle. Should a seller sell to the highest bidder, or is there some other standard, such as a morally defined price, to be applied? Charles R. Geisst traces the ways that philosophers, religious leaders, and economists have sought to answer that question, from antiquity through the modern era. Aristotle's thinking on usury influenced the idea of pricing well into the Renaissance. In his view, money was barren and should not be used to beget more money. As trade became more extensive, the strictures placed on pricing by Aristotelian thinking began to fall away, replaced by Roman and common-law conceptions of value and interest. Geisst's book follows the evolution of that thought-influenced along the way by figures such as Copernicus, Fibonacci, Adam Smith, Marx, Cassel, and Keynes-and charts parallel developments in European and Islamic notions of fair pricing. Today, pricing is seen as an economic inevitability, dictated by the laws of supply and demand. But this has not always been the case. As Geisst argues, the idea of a just price was once a moral concept, long before it was an economic one.